2017
DOI: 10.1016/j.nicl.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic depletion and basal forebrain volume in primary progressive aphasia

Abstract: Primary progressive aphasia (PPA) is a heterogeneous syndrome with various neuropathological causes for which no medical treatment with proven efficacy exists. Basal forebrain (BF) volume loss has been reported in PPA but its relation to cholinergic depletion is still unclear. The primary objective of this study was to investigate whether cholinergic alterations occur in PPA variants and how this relates to BF volume loss. An academic memory clinic based consecutive series of 11 PPA patients (five with the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
1
17
3
Order By: Relevance
“…We found that pathological increases in delta power uniquely contributed to classification into the PPA group, independent of volumetric and sex differences. One of the potential mechanisms of delta increases may be related to the depletion of cholinergic projections from the basal forebrain to the cortex (Schaeverbeke et al, ), although this mechanism is more pertinent to AD pathology and therefore to lvPPA than nfvPPA (Rohrer, Rossor, & Warren, ). Pathologic slowing of spectral activity has been reported in other clinical populations as well, for example, Stoffers et al () found slowing in both demented and non‐demented Parkinson's disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that pathological increases in delta power uniquely contributed to classification into the PPA group, independent of volumetric and sex differences. One of the potential mechanisms of delta increases may be related to the depletion of cholinergic projections from the basal forebrain to the cortex (Schaeverbeke et al, ), although this mechanism is more pertinent to AD pathology and therefore to lvPPA than nfvPPA (Rohrer, Rossor, & Warren, ). Pathologic slowing of spectral activity has been reported in other clinical populations as well, for example, Stoffers et al () found slowing in both demented and non‐demented Parkinson's disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…; Schaeverbeke et al . ). The resulting modulated gray matter volumes have been adjusted for overall brain size (total intracranial volume) by using the ‘nonlinear only’ component in the spatial normalization process for modulation of gray matter voxel intensities (Barnes et al .…”
Section: Methodsmentioning
confidence: 97%
“…Structural magnetic resonance imaging A structural T 1 -weighted MRI was acquired on a 3T Philips Achieva scanner (Philips, Best, The Netherlands) (3-D turbo field echo sequence, 32-channel Philips sensitivity encoding head coil: coronal inversion recovery prepared 3-D gradient-echo images, inversion time 900 ms, echo time/repetition time 4.6/9.6, flip angle 8°, voxel size 0.98 9 0.98 9 1.2 mm 3 ). Pre-processing of the T 1 -weighted MRI scans was performed with voxel-based morphometry (VBM8, http://dbm.neuro.uni-jena.de/vbmrunning) (Ashburner and Friston 2000) running on Statistical Parametric Mapping (SPM8, Wellcome Trust Centre for Neuroimaging, London, UK, http://www.fil.ion.uc l.ac.uk/spm) implemented in Matlab R2012b (Mathworks, Natick, MA, USA) as described in previous studies (Gillebert et al 2015;Schaeverbeke et al 2017). The resulting modulated gray matter volumes have been adjusted for overall brain size (total intracranial volume) by using the 'nonlinear only' component in the spatial normalization process for modulation of gray matter voxel intensities (Barnes et al 2010).…”
Section: Imaging Proceduresmentioning
confidence: 99%
“…All T 1 -weighted images underwent preprocessing with voxel-based morphometry (VBM8) [ 59 ] as previously described [ 60 , 61 ]. This included corrections for gradient nonlinearity and intensity inhomogeneity in the MRI.…”
Section: Methodsmentioning
confidence: 99%